Dynamic Perceived HIV Risk and Sexual Behaviors Among Young Women Enrolled in a PrEP Trial in Kenya: A Qualitative Study - Ngure, Kenneth; Thuo, Nicholas; Ogello, Vallery; Kiptinness, Catherine; Kamolloh, Kevin; Burns, Bridget Frances O'Rourke; Mugo, Nelly R.; Bukusi, Elizabeth A.; Garrison, Lindsey; Baeten, Jared M.; Haberer, Jessica E. (Frontiers in Reproductive Health, 2021)
Background: In Kenya and elsewhere in sub-Saharan Africa, young women are disproportionately affected by the HIV epidemic compared to young men. The extent to which young women’s self-perceptions about risk of HIV acquisition influence their sexual behaviors and use of HIV prevention methods remains unclear. We therefore conducted a qualitative study to explore these issues among young women enrolled in a pre-exposure prophylaxis (PrEP) trial. Methods: From January 2017 to January 2020, we conducted serial semi-structured in-depth interviews 50 purposively selected young women (18-24 years old) who were participating in the MPYA (Monitoring PrEP for Young Adult women) study— a randomized controlled trial in Thika and Kisumu, Kenya, assessing the impact of SMS reminders on PrEP adherence. Interviews were conducted at three time points (approximately one week, 3 months, and 12 months after initiating PrEP). We used an inductive, content analytic approach to identify key themes related to risk perceptions, sexual behavior, and use of HIV prevention tools. Results: Around the time of enrollment, most of the 50 women interviewed reported being at high risk of HIV because of their own sexual behaviors, such as inconsistent condom use, multiple sexual partners, and transactional sex. Additionally, high risk perception was based on the behavior of their partners, such as refusing to use condoms and being unsure of their partner’s HIV status. Young women’s perceived risk of HIV acquisition was a key motivator for PrEP initiation and continuation. During PrEP use, participants reported feeling protected and at less risk compared to peers who were not taking PrEP. Some reported no longer using condoms because they were confident that PrEP provided enough protection. Over time, many young women reported reducing risky sexual behaviors because of the regular counseling and HIV testing they received as part of their PrEP services. This lowered risk perception was in most cases accompanied by discontinuation of PrEP. Conclusions: HIV risk perception among young women in Kenya was dynamic and influenced their use of PrEP and condoms over time, suggesting an often-deliberate approach to HIV prevention and sexual health.